(untitled) (Papeles, 2024)
Introduction: Social practices are studied by the relationships established between the people who participate in their construction in each space. The field of secondary education is one of the spaces where these practices are generated and structured according to the position and interest of the agents in the processes of interaction in which they participate, thus generating a sort of encounter that challenges our thinking by the meaning assigned by each of the individuals who participate in the social links created in a defined space of interaction. Social practices, the teacher and secondary education become elements of inquiry due to their relevance in school processes, which in turn are being affected by factors external to the school dynamics. Methodology: Used for this purpose is based on a documentary review of the categories mentioned to identify the study trends that address the subject, seeking to understand and compare the way in which the teacher and the teaching profession are thought of in the international, regional, and national context. Results and discussion: In the review of the selected bibliographic sources, it is observed that the trend of practices revolves around the pedagogical component, while the social aspect is explored in depth from the sociological field. About teachers, it seems that teacher discomfort is generalized, in the understanding that their claims are similar in different parts of the world. Conclusions: The article closes by highlighting the relevant concepts of the categories addressed.